Bicarbonate-buffered solution versus Plasma-Lyte in orthotopic adult liver transplantation: a pilot open-label, randomized, non-inferiority trial - Fumitaka Yanase; Laurence Weinberg; Michael Jiang; Varun Peri; Rebecca Caragata; Jian Wen Chan; Lachlan F. Miles; Shervin Tosif; Louise Ellard; Peter McCall; Brett Pearce; David A. Story; et al. (Korean Journal of Anesthesiology, 2025)
Background The ideal intravenous maintenance and resuscitation fluid for patients undergoing orthotopic liver transplantation (OLT) remains unknown. We aimed to determine whether bicarbonate-buffered solution was non-inferior to Plasma-LyteTM in preventing metabolic acidosis during OLT. Methods We conducted a pilot single-center, open-label, randomized trial to compare the physiological effects of intravascular volume maintenance with a bicarbonate-buffered solution vs. Plasma-LyteTM in adults undergoing OLT. Non-inferiority was defined as a median difference in the standard base excess (SBE) of less than −2.5 mEq/L. The primary endpoint was the SBE at 5 minutes post-reperfusion. Quantile regression analysis was applied to confirm non-inferiority. Secondary endpoints included other forms of acid-base and electrolyte imbalances at pre-specified time points and postoperative complications. Results We randomized 52 adults undergoing OLT. The median (Q1, Q3) volume infused was 5 000 (3 125, 7 000) ml in the bicarbonate-buffered solution group and 5 500 (4 000, 10 500) ml in the Plasma-LyteTM group (P = 0.37). The median (Q1, Q3) SBE at 5 minutes post-reperfusion was −4.857 (−6.231, −3.565) mEq/L in patients receiving bicarbonate-buffered solution and −4.749 (−7.574, −2.963) mEq/L amongst those in the Plasma-LyteTM group. The estimated median difference by quantile regression was −0.043 mEq/L (95% CI [−1.988 to 1.902] mEq/L; one-sided P = 0.015). There were no significant differences in the acid-base secondary outcomes, number of complications, or patient mortality. There were no reported adverse events or safety concerns associated with the use of either solution. Conclusions A bicarbonate-buffered solution was non-inferior to Plasma-LyteTM for maintaining acid-base homeostasis post-reperfusion in OLT patients.